Evaluation of sorafenib in Chinese unresectable hepatocellular carcinoma patients with prior surgery and portal vein tumor thrombosis: A subset analysis of GIDEON study data - Sheng-Long Ye; Xiaoping Chen; Jiamei Yang; Ping Bie; Shuijun Zhang; Fengyong Liu; Luming Liu; Jie Zhou; Kefeng Dou; Christina SM Yip; Xiaolei Yang (Tumor Biology)
The purpose of this study was to examine the safety and efficacy of sorafenib in Chinese patients with unresectable hepatocellular carcinoma. Data of 338 Chinese patients from the Global Investigation of therapeutic DEcisions in hepatocellular carcinoma and Of its treatment with sorafeNib study database were included. Patients were divided into those who received and did not receive sorafenib prior to surgical resection and those with and without portal vein tumor thrombosis. In the non-surgery group, the median survival was 302 days (95% confidence interval: 244–371), and the median time from diagnosis to death was 428 days (95% confidence interval: 352–556); in the surgery group, half of the patients survived for 345 days and the median time from diagnosis to death was 1000 days (95% confidence interval: 750–2816). Median progression-free survival and median time to progression were not different between the two groups. Median overall survival was 360 days (95% confidence interval: 309–435) in the non–portal vein tumor thrombosis group and 240 days (95% confidence interval: 181–296) in the portal vein tumor thrombosis group; median time between hepatocellular carcinoma diagnosis and death was 750 days (95% confidence interval: 472–1000) and 420 days (95% confidence interval: 252–567), respectively, in the two groups. Median progression-free survival was 209 days (95% confidence interval: 166–264) for patients without portal vein tumor thrombosis and 154 days (95% confidence interval: 112–202) for patients with portal vein tumor thrombosis; median time to progression was 295 days (95% confidence interval: 209–463) and 221 days, respectively. Adverse events were generally comparable regardless of prior surgery and portal vein tumor thrombosis status. We thus conclude that earlier administration of sorafenib may result in improved outcomes in patients with unresectable hepatocellular carcinoma and portal vein tumor thrombosis.